MOTIVASI SUKSES MENUJU DUNIA KERJA BAGI SISWA KELAS XII SMK BINA MITRA CIKARANG - Prabandari, Sari; Kaban, Karya Bakti; Widiarti Lestariningsih; Diand Mardiana; Fera Lufhidarani Pranita (PUBLICA: Jurnal Pengabdian Kepada Masyarakat, 2022)
World of work could be a company, institution or organization where people do something for making money. Many factors influence the success in the world of work, such as: passion, brain, beauty, discipline, behaviour and motivation. Motivation is a set of value that influence an individual to achieve a personal specific target. Success can be defined as an achievement in a certain field. The motivation in the world of work is needed to push someone optimizing his ability and potency. The graduates of SMK (Vocational High School) are designed to be placed in the world of work. It is to be important thing to grow the success motivation on the students of vocational high school (SMK).